(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe clinical and paraclinical characteristics of respiratory distress syndrome in premature infants with endothelial disease and evaluate the results of treatment with Surfactant technique at Hung Yen Obstetrics and Children’s Hospital in 2020 - 2021. Subjects-methods: Design of a cross-sectional descriptive study comparing before and after Surfactant treatment. All premature infants with diagnosis confirmed treated with surfactant (Curosurf). Administer curosurf 116mg/1 vial single dose for premature infants at a dose of 100- 160 mg/kg. Choose a convenient sample size for preterm infants who are eligible for the study. Results: 98% of children breath well. Amniotic fluid in 94.9%; respiratory failure early in the first hour (Silverman score >6). Exhausted breathing; moaning 82.4%, retraction 79.4%, SpO2 below 90% was 91.8% and 8.2% of children had hypothermia. There is grade 3 X-ray damage. Heart rate, breathing rate, and FiO2 after 6 hours of treatment all decreased statistically significantly (p<0.05). Conclusions: Respiratory distress in premature infants appeared within 1 hour of birth (70.7%). Surfactant treatment markedly reduced the need for FiO2. Lung lesions on chest X-ray improved well. It is necessary to examine and manage pregnancy well to avoid premature delivery.